2000
DOI: 10.1002/(sici)1097-0215(20000415)86:2<204::aid-ijc9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased gelatinase-A and gelatinase-B activities in malignantvs. benign breast tumors

Abstract: Matrix metalloproteinases (MMP) types 2 and 9 (also known as gelatinase A and B) are thought to be causally involved in cancer invasion and metastasis. In normal as well as in malignant tissue, both these MMPs occur in multiple forms such as inactive precursors, active enzymes and enzyme‐inhibitor complexes. Using newly developed quantitative activity assays, the levels of active MMP‐2, total (active and activatable) MMP‐2 and total MMP‐9 were found to be significantly higher in breast carcinomas than in fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 16 publications
3
74
2
1
Order By: Relevance
“…In several tumors, MMPs have been linked to tumor growth, metastasis and clinical outcome [7,10,[18][19][20]23,[81][82][83]. It has also been shown that proMMP-2 and proMMP-9 expression is increased in malignant cancers compared to benign cancers [84][85][86].…”
Section: The Role Of Mmps In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In several tumors, MMPs have been linked to tumor growth, metastasis and clinical outcome [7,10,[18][19][20]23,[81][82][83]. It has also been shown that proMMP-2 and proMMP-9 expression is increased in malignant cancers compared to benign cancers [84][85][86].…”
Section: The Role Of Mmps In Cancermentioning
confidence: 99%
“…A number of studies have linked elevated MMP-2 and -9 expression to increased metastasis and tumor stage, e.g. malignant versus benign breast tumors and advanced ovarian tumors versus benign [84][85][86]. In several invasive cell lines, MMP-9 expression was increased compared to non-invasive counterparts [154,155].…”
Section: The Role Of Mmps In Metastasismentioning
confidence: 99%
“…Indeed, an increase in MMP-9 secretion has been shown to enhance the invasive capacities of breast cancer cells (Johansson et al, 2000). Moreover, MMP-9 was detected more frequently in malignant breast carcinoma than in benign tumour (Rha et al, 1997;Hanemaaijer et al, 2000). However, the role of MMP-9 is less clear than that of u-PA, as overexpression of MMP-9 in human breast cancer was reported to be a favourable indicator in node-negative patients (Scorilas et al, 2001).…”
Section: Cooperation Between Monocytes and Breast Cancer Cells E Blotmentioning
confidence: 99%
“…Both tumor cell and stromal tissues in breast cancer tissue have been reported to have increased MMP-9 expression (Ranogajec et al, 2012). A considerable number of studies have proved that high MMP-9 expression is related to tumor stage and lymph node metastasis in breast cancer patients (Hanemaaijer et al, 2000;Hao et al, 2007;Gu et al, 2009). Furthermore, Oscar and sullu have indicated a significant association between high MMP-9 expression and poor survival result in breast cancer patients (Sullu et al, 2011;Oscar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%